The Influence of Digital Marketing Via Instagram Ads and Product Quality on Increasing Sales in Rigis Jaya Coffee Lampung Barat - Azhari, Imam; Sari, Wenny Permata (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of variables such as digital marketing and product quality on increasing Rigis Jaya West Lampung coffee sales. The population that is the focus of the research is all Rigis Jaya West Lampung coffee consumers using a sample of 100 respondents from Rigis Jaya West Lampung coffee consumers using a purposive sampling technique. The analytical method used is multiple linear regression. The findings from this research show that digital marketing and product quality have a partially significant effect on increasing sales. Simultaneously or together, digital marketing variables and product quality significantly increase sales and provide a variation between variables of 77.4%. This research recommends that Rigis Jaya West Lampung Coffee is expected to be active in using social media Instagram ads as a promotional medium to increase sales. Apart from that, it is also hoped that this research can be used as a reference for further research related to the influence of digital marketing, product quality, and increasing sales.